The Influencing Factors of Impulsive Buying Behaviour in Transmart Carrefour Sidoarjo - Oscarius Yudhi Ari Wijaya; Elia Ardyan (Binus Business Review, 2018)
This research examined the influence of money availability and idea shopping on impulsive buying behavior. This research was a type of associative-conclusive research to test the magnitude of the influence of money availability directly to impulsive buying behavior or indirectly through idea shopping as an intervening variable. This research used 218 respondents who made unplanned purchases spontaneously and suddenly. This research used Structural Equation Modeling (SEM) method based on General Structured Component Analysis (GSCA). The data used to test the hypothesis were obtained from the results of the distribution of questionnaires. This research finds there is good direct influence between money availability and impulsive buying behavior, or indirectly through idea shopping as an intervening variable. There are several recommendations for the company. First, the salesman should be more intensive in interacting with consumers to influence them. Second, the salesman in each outletmust have good communication skills.